Kouluterveys 2013 : pääkaupunkiseudun raportti - Luopa, Pauliina; Kivimäki, Hanne; Nipuli, Suvi; Vilkki, Suvi; Jokela, Jukka; Laukkarinen, Essi; Paananen, Reija; Normann, Maria (Terveyden ja hyvinvoinnin laitos & Pääkaupunkiseudun kouluterveyskyselytyöryhmä, 2013)
Sammandrag
Keywords: terveystutkimus; koululaiset; terveyskäyttäytyminen; kouluterveydenhuolto; pääkaupunkiseutu (Suomi); Helsinki; Espoo; Vantaa; Kauniainen